2021
DOI: 10.1186/s13104-021-05639-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between interpersonal support and retention in HIV care among HIV+ nursing mothers in Uganda

Abstract: Objective The global burden of HIV on women and pediatric populations are severe in sub-Saharan Africa. Global child HIV infection rates have declined, but this rate remains quite high in sub-Saharan Africa due to Mother-to-child transmission (MTCT). To prevent MTCT of HIV, postpartum women living with HIV (WLHIV) are required to return to a health facility for HIV care within 60 days after childbirth (Retention in HIV care). Studies suggest that interpersonal support was positively associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…Given these documented benefits, an intervention to strengthen interpersonal support could help improve ART adherence outcomes among PLHW, especially those in urban areas, concurrent with findings of previous interpersonal support interventions [ 25 , 45 ]. However, this finding is contrary to the results of a recent study in the Greater Accra Region of Ghana and Uganda, which showed interpersonal support from family and friends had no association with adherence [ 21 , 46 ].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Given these documented benefits, an intervention to strengthen interpersonal support could help improve ART adherence outcomes among PLHW, especially those in urban areas, concurrent with findings of previous interpersonal support interventions [ 25 , 45 ]. However, this finding is contrary to the results of a recent study in the Greater Accra Region of Ghana and Uganda, which showed interpersonal support from family and friends had no association with adherence [ 21 , 46 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Additionally, PLWH should remain in care for a lifetime, regardless of CD4 count or viral load [ 13 , 14 ]. Many PLWH in low-resourced countries do not take full advantage of ART services because of individual factors (e.g., depression, internalized stigma, poor attitudes and beliefs, forgetting to take ART, ART side effects, financial difficulty) [ 7 , 15 − 18 ], community factors (e.g., family and community norms or lack of social support) [ 19 – 21 ], and healthcare factors (e.g. inaccessibility of services) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, fear of experiencing stigma is found to be a major factor preventing PLWH from disclosing their serostatus to partners and family members. This is consistent with other studies which found that PLWH who disclose their HIV status experience stigma from their family compared to those who do not disclose their status [ 37 , 41 43 ]. This highlights the importance of designing multilevel stigma reduction interventions that not only focus on PLWH but also on their family, partners, and community.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior studies [ 31 33 ], results in our study also indicate that none of those who had low internalized stigma reported depression symptoms, while those with high stigma reported more depressive symptoms, suggesting that stigma is associated positively with depression. Previous studies have reported associations between HIV-related stigma and negative health outcomes specifically [ 34 37 ]. Participants in our study also described how stigma impacted their mental health and engagement in care.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical assumptions suggest a positive relationship, indicating that increased social support should enhance adherence rates. However, existing research has yielded conflicting findings, with some studies supporting this assumption [ 13 , 14 ], while others have reported negative associations [ 15 , 16 ] or no significant relationship at all [ 11 ]. These inconsistencies necessitate a deeper investigation into the complex interplay between social support and ART adherence, especially in a different social group of HIV patients.…”
Section: Introductionmentioning
confidence: 99%